2018
DOI: 10.3390/jcm7050106
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Self-Perception of Old Age on the Effect of a Healthy Aging Program

Abstract: It has been shown that health programs are useful for the prevention and control of chronic diseases in community-dwelling older people; however, a negative self-perception of old age could have an effect on the results. Therefore, our aim was to evaluate the effect of a healthy aging program linked to self-perception of old age in Mexican community-dwelling older people. A pre-test/post-test single-group design study was conducted in a convenience sample of 64 older people who undertook the entire healthy agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…Moreover, QOL was significantly positively associated with self-rated health, selfperception, and education. Here, our results align with Maniscalco et al who found a correlation between QOL and self-rated health in a sample of individuals aged 50 and older, while according to Mendoza-Núñez et al [33], older adults' self-perception of old age influences their health. Ruppe et al [31] showed that older adults' socioeconomic status (including education) is strongly associated with their participants' QOL.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, QOL was significantly positively associated with self-rated health, selfperception, and education. Here, our results align with Maniscalco et al who found a correlation between QOL and self-rated health in a sample of individuals aged 50 and older, while according to Mendoza-Núñez et al [33], older adults' self-perception of old age influences their health. Ruppe et al [31] showed that older adults' socioeconomic status (including education) is strongly associated with their participants' QOL.…”
Section: Discussionsupporting
confidence: 92%
“…First, for both husbands and wives, almost all their health conditions declined when their own SPA became more negative. These results should not be surprising, given that numerous studies have shown that negative SPA predict decline in physical, mental, cognitive, and subjective health (Gu et al, 2016;Levy, Slade, & Kunkel, 2002;Mendoza-Núñez et al, 2018;Mohammadpour et al, 2018;Moser et al, 2011;Seidler & Wolff, 2017). Further, the recent comprehensive review indicates that among the three components of ageism, the prevalence of significant relationships with health was the highest when ageism was operationalized as negative SPA as opposed to age stereotypes and age discrimination (Chang et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…The old age is a period of life that begins at age 60 and is a biological process that all living beings, including humans, experience it [2]. This period, with all of its consequences for the individuals and society, has created major challenges for all communities [3]. The elderly people are at risk of potential threats, such as increased chronic diseases, loneliness, isolation, and lack of social support [4].…”
Section: Introductionmentioning
confidence: 99%